PENERAPAN STRICT LIABILITY DALAM PENANGGULANGAN TINDAK PIDANA PEMBAKARAN HUTAN OLEH DIREKTORAT RESERSE KRIMINAL KHUSUS KEPOLISIAN DAERAH RIAU BERDASARKAN UNDANG-UNDANG NOMOR 18 TAHUN 2013 TENTANG PENCEGAHAN DAN PEMBERANTASAN PERUSAKAN HUTAN - Adeliasari, Sy. Rezi; Edorita, Widia; ', Erdianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Strict liability is a liability without fault, where the perpetrator can already be punished if he has committed a criminal act as has been formulated in the law without seeing how his inner attitude. Forest fires can cause forest destruction and the perpetrators are not only individuals but also by corporations. If the principle of strict liability can be enforced in combating forest burning will provide benefits: (1) bussiness actors undertaking bussiness activities have an enormous impact on their licensing, will be more responsible. Not only responsible to local residents but also to environmental impacts, liability of suspects or companies. (2) strict liability is also able to provide effectiveness to the concept of subtainable development that is not just an appeal but as an order that must be obeyed by business actors.The issue discussed are first, as to whether the strict liability principle can be applied in cases of forest fires in the province, second on whether the application of strict liability constraints in combating forest fires by the special criminal police crime directorate of Riau based on the law number 18 of 2013 on the prevention and eradication of forest destruction, third about how the efforts undertaken by the special criminal investigation directorate of the Riau regional police in combating the act of combustion of forest based on the law number 18 of 2013 on the prevention and eradication of forest destruction.The research method used is empirical research, another term used is sociological legal research called field research and research is descriptive. In data collection, the type of data used in this study is primary and secondary data, ie directly through written data and interviews from the Directorate of Special Criminal Investigation of Riau Regional Police, Law No. 18 of 2013 on Prevention and Eradication of Forest Destruction, Law Number 32 Year 2009 on Environmental Protection and Management, legal journals and research related books. The data analysis is done qualitatively and deductively deduced.From the results of research conducted by the authors of the application of strict liability in the prevention of criminal acts of forest burning has been implemented but there are still many individuals and corporate actors who do not conduct criminal responsibility as appropriate, such as accountability on the principle of strict liability.Keywords: strict liability – Countermeasures –Forest Burning